Efficacy of calcein as a chemical marker of Potamocorbula laevis - Gao, Jin; Xie, Xi; Liu, Xiang-Feng; Bai, Yong-An; Yang, Miao; Teng, Wei-Ming; Liu, Hai-Jiao; Wang, Qing-Zhi (Frontiers in Marine Science, 2024)
Introduction Calcein was used to develop a shell marking method for Potamocorbula laevis. Methods The suitable conditions for marking were investigated, including marking concentration, immersion time, and water temperature. The impacts and feasibility of the marking method were assessed based on the survival rate of P. laevis, the success rate of fluorescence marking, marking quality, and alterations in activities of antioxidant enzymes in the digestive gland of the experimental bivalves. Two concentrations of calcein (20 and 50 mg/L) were used and the immersion time included 1 and 2 h, respectively. The experiment was performed in two rounds, with water temperatures of 12.84 ± 0.09 and 24.18 ± 0.04 °C, respectively. Results and discussion The results indicated that calcein did not significantly impact the survival of P. laevis after 7 d of recovery. The catalase activity and malondialdehyde content in low temperature-marked P. laevis showed significant decreases, and the relative abundances of certain fatty acids also exhibited significant changes within 2 h post exposure to 20 mg/L of calcein. However, these indicators returned to normal levels within 7 d. The marking impact of calcein was proportional to the calcein concentration and immersion time. Higher temperature generated a negative impact on the marking effect of 20 mg/L of calcein, while no obvious impacts were observed for 50 mg/L of calcein. The marking success rates and the recapture rates of P. laevis for in situ tests in the two experimental groups were both 100% and 4.44 ± 1.29% after one month. Also, the recapture marking rates and the marking good rates of the recaptured individuals were both 100%. There were no significant differences between these parameters for 50 and 75 mg/L of calcein. Given the cost and safety of labeling, a strategy in terms of an immersion in 50 mg/L of calcein for 2 h could be considered as an effective in situ labeling scheme for P. laevis. In conclusion, calcein can be employed as a marking method for P. laevis. These findings could be potentially beneficial for development of in situ labeling technology, proliferation as well as release of shellfish in tidal flats and resource conservation.